+0  
 
0
61
1
avatar+76 

Suppose \(f(x)=\frac{3}{2-x}\). If \(g(x)=\frac{1}{f^{-1}(x)}+9\), find \(g(3)\).

 Apr 8, 2021
 #1
avatar+118625 
+1

We    can  write

 

y =  3 / ( 2 -x)            get  x  by itself

 

y ( 2 - x)   =   3

 

2y  - yx  =  3

 

yx  = 2y  -  3

 

x  =   (2y - 3)  / y              "swap"   x  and y

 

y    =  ( 2x - 3)   / x  =    f-1(x)

 

g(x)  =     1 / ( (2x - 3) / x )  +  9   =    x / ( 2x - 3)   +  9

 

So

 

g (3)   =      3  / ( 2*3 - 3)  +  9  =    3 / (6-3)   +  9   =    3 / 3   +  9  =   1 + 9   =  10

 

 

cool cool cool

 Apr 8, 2021

62 Online Users

avatar
avatar
avatar
avatar